2015
DOI: 10.1111/aas.12518
|View full text |Cite
|
Sign up to set email alerts
|

Positive end‐expiratory pressure titration at bedside using electrical impedance tomography in post‐operative cardiac surgery patients

Abstract: During a short descending PEEP trial at bedside, EIT is capable of following the status of regional ventilation distribution in ventilated patients. The 'best' PEEP value identified by individual maximum CRS was lower than optimal PEEP levels as determined by means of EIT indices. EIT could help setting PEEP in post-operative ventilated patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(32 citation statements)
references
References 27 publications
1
29
0
2
Order By: Relevance
“…These measures have most often been derived from the decremental PEEP-titration manoeuvre. [73][74][75] Figure 3 shows an example patient examination during this manoeuvre. By sequentially measuring the EIT-derived regional C rs , it is possible to quantify the amounts of tissue that (a) recollapse during the trial, excluding them from ventilation and (b) are brought back to adequate ventilation, previously impaired by hyperdistension.…”
Section: Monitoring Of Mechanical Ventilationmentioning
confidence: 99%
“…These measures have most often been derived from the decremental PEEP-titration manoeuvre. [73][74][75] Figure 3 shows an example patient examination during this manoeuvre. By sequentially measuring the EIT-derived regional C rs , it is possible to quantify the amounts of tissue that (a) recollapse during the trial, excluding them from ventilation and (b) are brought back to adequate ventilation, previously impaired by hyperdistension.…”
Section: Monitoring Of Mechanical Ventilationmentioning
confidence: 99%
“…It is been previously confirmed that ideal levels of PEEP may minimize the risk of ventilator-associated lung injury, thus reduce the duration of mechanical ventilation and ICU stay (Karsten et al 2015). Out study introduced a non-invasive measure to help select an ideal PEEP to achieve better outcomes without causing severe side effects in cardiovascular system.…”
Section: Discussionmentioning
confidence: 93%
“…At this time there are different views on the matter. Lachmann introduced the “open lung concept” applying higher levels of PEEP to keep the lungs open while others focus their ventilator settings on avoiding overdistension secondary to high PEEP levels, or define optimal PEEP as the lowest level of alveolar overdistension and collapse [1922]. The PEEP level using a more open lung approach with CL less than 3 or 1% are presented as supplementary material.…”
Section: Discussionmentioning
confidence: 99%
“…Optimal PEEP was determined as the best compromise between alveolar overdistension and alveolar collapse by off-line analysis of changes in regional compliance during each PEEP step in the decremental part of the PEEP trial. This means the best regional compliance to maximize recruitment of the dependent lung and minimize overdistension of nondependent lung areas [18, 19] (Fig. 2).…”
Section: Methodsmentioning
confidence: 99%